Harnessing Implementation Science and Self-Determination Theory in Participatory Research to Advance Global Legume Productivity - Payne, Simon Mark; Nicholas-Davies, Phillipa; Home, Robert (Frontiers in Sustainable Food Systems, 2019)
There are many challenges associated with increasing global legume production, and to overcome them will require stakeholders to modify certain perceptions and behaviours. Unfortunately, stakeholder motivation has been under-appreciated in global legumes research, despite its central role as a predictor of research uptake. Observational studies exist but often, motivation theory is wielded with a lack of conviction, and intervention studies have not yet emerged. Thus, participatory intervention research that embeds insight from contemporary understandings of motivated behaviour, is a fruitful line of investigation. Participatory/transdisciplinary, reflective learning methodologies have demonstrated an ability to create new, and maximise existing, pathways to impact in legume productivity. Conversely, successes from the burgeoning field of implementation science have yet to be translated to agriculture research; frameworks exist that simplify the researcher’s task of planning, applying, reporting, and replicating their transdisciplinary research. This review describes a novel methodological approach which promotes cross-fertilisation of ideas between scientific, extension, farmer, and industry co-actors, engendering a dynamic learning culture; partners co-plan, co-execute, and co-disseminate their work together, in an equitable arrangement. This ensures that outputs are targeted to the needs of end-users and that both scientific and practical (local) knowledge is taken into account. Despite a recent proliferation of useful articles on knowledge co-creation in sustainable agriculture, this review is the first to rationalise to researchers the need to design participatory research which is informed by social psychology (Self-Determination Theory) and adheres to procedures championed in implementation science (e.g., feasibility and fidelity studies, systematic reporting). Theoretical rigour is added to the participatory research agenda, but this review also offers some practical suggestions for application in legumes research. While the focus is on legumes, this guidance is equally applicable to other crops and agricultural systems.